2007
DOI: 10.1111/j.1751-7893.2007.00014.x
|View full text |Cite
|
Sign up to set email alerts
|

Social and symptomatic outcomes of first‐episode bipolar psychoses in an early intervention service

Abstract: Aim: We aimed to establish the relative proportions of all diagnoses in people aged 14-35 years presenting to an early intervention in psychosis service, and to compare demographic variables, symptoms and outcomes between the bipolar psychoses and other psychoses at 3-6 months and 1 year post referral. Methods:Prospective 3-to 6-month diagnostic and symptomatic assessments were carried out. Diagnoses were established using the Diagnostic Interview for Psychoses -Diagnostic Module. Symptoms and outcomes were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…As cases in the affective and non-affective psychosis groups were well matched on clinical and social factors, the differences observed between these two groups are unlikely to be due to variables such as duration of either illness or unemployment. The findings may be more consistent with our recent observations, and those of others, that bipolar disorder cases respond rapidly and with good social recovery outcomes to early intervention services compared with non-affective psychosis (Macmillan et al 2007).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As cases in the affective and non-affective psychosis groups were well matched on clinical and social factors, the differences observed between these two groups are unlikely to be due to variables such as duration of either illness or unemployment. The findings may be more consistent with our recent observations, and those of others, that bipolar disorder cases respond rapidly and with good social recovery outcomes to early intervention services compared with non-affective psychosis (Macmillan et al 2007).…”
Section: Discussionsupporting
confidence: 92%
“…Our aim was also to clarify and define selection criteria and we therefore included people with both affective and non-affective psychosis. Previous studies have shown that people with affective psychosis tend to make better recoveries after the first episode (Macmillan et al 2007) and have better social outcomes generally than people with non-affective psychosis (Werry et al 1991; Cannon et al 1997; Jarbin et al 2003). We therefore aimed to explore the differential effect of the intervention on affective and non-affective psychosis.…”
Section: Introductionmentioning
confidence: 99%
“…Affective psychoses represent a substantial proportion (~31%) of EP service users. 23 A restricted positive symptom focus will invariably result in inadequate treatment of manic episodes. Depression is also often overlooked in people presenting with psychosis.…”
mentioning
confidence: 99%